Strategizing urbanism in the era of neoliberalization: State power reshuffling, land development and municipal finance in urbanizing China. (August 2015) - Lin, George CS; Li, Xun; Yang, Fiona F; Hu, Fox ZY
This paper examines the new dynamism of China's urbanization in which urbanism has been actively pursued by municipal governments as a strategy to negotiate and contest with the new power relations established by the post-reform regime in the era of neoliberalization. The research identifies the salient features of urbanization and urban land development since the 1990s, probes into their social and political origins, and evaluates the effects of Chinese urban revolutions from above on economic growth, regional inequality and social volatility. The data analysed include those gathered from the national level and from the Guangzhou metropolis in southern China. The interwoven processes of state power reshuffling, urban land development and municipal finance in contemporary China are believed to have constituted a significant and controversial case for critical evaluation of the political origins of urban revolutions in the age of global urbanism and their uneven socioeconomic consequences.